2018
DOI: 10.48550/arxiv.1810.09153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blow-up of the radially symmetric solutions for the quadratic nonlinear Schrödinger system without mass-resonance

Abstract: We consider the quadratic nonlinear Schrödinger systemwhere 1 ≤ d ≤ 6 and κ > 0. In the lower dimensional case d = 1, 2, 3, it is known that the H 1 -solution is global in time. On the other hand, there are finite time blow-up solutions when d = 4, 5, 6 and κ = 1/2. The condition of κ = 1/2 is called mass-resonance. In this paper, we prove finite time blow-up under radially symmetric assumption when d = 5, 6 and κ = 1/2 and we show blow-up or grow-up when d = 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In [18] the authors, among other things, proved the existence of ground state solutions for (1.4), when κ > 0, and used these solutions to give a sharp criterion for the existence of global H 1 solutions in the mass-resonance case and n = 4. This kind of result was extended to the non-mass-resonance case (κ = 1 2 ) in [23], where the authors showed a blow-up result when the initial data is radial in dimensions n = 5 and n = 6. Some very recent works without mass-resonance condition have been appeared.…”
Section: (H1)mentioning
confidence: 78%
See 1 more Smart Citation
“…In [18] the authors, among other things, proved the existence of ground state solutions for (1.4), when κ > 0, and used these solutions to give a sharp criterion for the existence of global H 1 solutions in the mass-resonance case and n = 4. This kind of result was extended to the non-mass-resonance case (κ = 1 2 ) in [23], where the authors showed a blow-up result when the initial data is radial in dimensions n = 5 and n = 6. Some very recent works without mass-resonance condition have been appeared.…”
Section: (H1)mentioning
confidence: 78%
“…From the mathematical point of view the interest in nonlinear Schrödinger systems with quadratic interactions has been increased in the past few years (see [7], [8], [15], [17], [18], [23], [24], [25], [33], [34], [36], [39] and references therein). So, in [34] we initiated the study of system (1.1) with general quadratic-type nonlinearities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the second author, Kishimoto, and the third author [11] obtained the scattering below the ground state in the L 2 -critical case, i.e., d = 4, under the assumption of radial symmetry. Moreover, they also showed the finite time blow-up result below the ground state under the assumption of radial symmetry in [12].…”
mentioning
confidence: 91%
“…Remark 1.1. In the opposite case , i.e., K(u 0 , v 0 ) < 0, the second author, Kishimoto, and the third author [12] show that the finite time blow-up occurs in both time directions. And so, the behavior of the radially symmetric solution to (NLS) below the ground state completely determined by the sign of the functional K at initial time.…”
mentioning
confidence: 99%
“…The proof of the blowing-up or growing-up result without radially symmetric assumption is based on the argument by Du-Wu-Zhang in [6]. We can exclude the possibility of the growing-up result by the argument in [23], [15], and [10] if "the data and the potential are radially symmetric" or "the data has finite variance".…”
mentioning
confidence: 99%